An improved Sudoku-based data hiding scheme using greedy method. (22nd September 2020) - Chang, Chin-Chen; Su, Guo-Dong; Lin, Chia-Chen
Inspired by Chang et al.'s scheme, an improved Sudoku-based data hiding scheme is proposed here. The major idea of our improved scheme is to find the approximate optimal solution of Sudoku using the greedy method instead of via a brute-force search for an optimal solution. Later, the found approximate optimal solution of Sudoku is used to offer satisfactory visual stego-image quality with a lower execution time during the embedding procedure. Simulation results confirmed that the average stego-image quality is enhanced by around 90.51% compared to Hong et al.'s scheme, with relatively less execution time compared to a brute-force search method.